Morphometry of podocytes – a single center study of pediatric patients: is there any correlation with proteinuria level? - Diana DEREWICZ; Roxana TARAS; Cosmin FLORESCU; Mihaela BALGRADEAN; Maria SAJIN (Archives of the Balkan Medical Union, 2019)
Introduction. The most common diagnosis after a kidney biopsy in pediatric population is minimal change disease. When the prognosis is not favorable in spite of the minimal change disease diagnosis, there is a clinical suspicion of focal segmental glomerulosclerosis.